2017
DOI: 10.1371/journal.pone.0185500
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of cost-effectiveness studies comparing conventional, biological and surgical interventions for inflammatory bowel disease

Abstract: BackgroundInflammatory bowel disease (IBD) is a chronic disease placing a large health and economic burden on health systems worldwide. The treatment landscape is complex with multiple strategies to induce and maintain remission while avoiding long-term complications. The extent to which rising treatment costs, due to expensive biologic agents, are offset by improved outcomes and fewer hospitalisations and surgeries needs to be evaluated. This systematic review aimed to assess the cost-effectiveness of treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 85 publications
1
83
0
Order By: Relevance
“…ORIgInal aRTIClE remission periods. However, many patients are refractory, so that surgery remains their only alternative [13]. The partial inefficacy of pharmacological interventions and the unresponsiveness of some subjects has spurred clinical interest in developing other approaches for effectively controlling IBD.…”
Section: Clinical and Experimental Immunologymentioning
confidence: 99%
See 1 more Smart Citation
“…ORIgInal aRTIClE remission periods. However, many patients are refractory, so that surgery remains their only alternative [13]. The partial inefficacy of pharmacological interventions and the unresponsiveness of some subjects has spurred clinical interest in developing other approaches for effectively controlling IBD.…”
Section: Clinical and Experimental Immunologymentioning
confidence: 99%
“…IBD response is driven by cytokines and leukocyte infiltrate in the gut [5][6][7], with histological features of crypt cell hyperplasia, interstitial edema and mucosa ulcerations [8]. However, many patients are refractory, so that surgery remains their only alternative [13]. Accordingly, current available treatments are aimed at reducing inflammation in an attempt to avoid disease recurrence or to prolong clinical Clinical and Experimental Immunology ORIgInal aRTIClE remission periods.…”
Section: Introductionmentioning
confidence: 99%
“…The cost-effectiveness of early biologic treatment in IBD is also being explored [135], whereas a model extrapolating data from the CALM trial in CD showed that "tight control," using biomarkers to direct adalimumab treatment, was cost-effective versus standard clinical management over 2-and 5-year timeframes, with cost-effectiveness improving over time [136]. Biosimilar uptake may also bring indirect economic benefits, often not considered in cost-effectiveness analyses [137]. In RA, effective early treatment with DMARDs [138] or biologics [139] can improve workforce productivity, with economic benefits for individuals and society.…”
Section: Pharmacoeconomists' Perspective: Cost Of and Access To Biolomentioning
confidence: 99%
“…Over time, the outcomes from using these drugs in the right patients, with the right targets, at the right dose and with the right combinations have incrementally improved . The cost reductions, now being seen with the availability of biosimilars, will further improve the cost‐effectiveness of this class . Finally, the identification of predictive biomarkers may lead to a more personalised approach to the use of these agents …”
mentioning
confidence: 99%
“…8 The cost reductions, now being seen with the availability of biosimilars, will further improve the cost-effectiveness of this class. 9 Finally, the identification of predictive biomarkers may lead to a more personalised approach to the use of these agents. 10 Improvements in IBD outcomes over a decade may have many causes.…”
mentioning
confidence: 99%